Análise geoambiental da região de marília, SP: Suscetibilidade a processos erosivos frente ao histórico de ocupação da área - Bezerra, Maria Ângela; Etchebehere, Mario Lincoln de Carlos; Saad, Antonio Roberto [UNESP]; Casado, Fabio da Costa (My University, 2009)
The study area comprises the western portion of the Marília Plateau, State of São Paulo, southeastern Brazil. The geological substrate encompasses Cretaceous sedimentary rocks of the Bauru Group and local Neocenozoic units like colluvium aprons, fluvial terrace deposits, in situ regoliths, and modern alluvial deposits. In a geomorphologic sense, the study area might be characterized as showing two main pediplanes, viz. P1 Surface (upper) and P2 Surface (lower), both surfaces are presently under dissecation processes. After the 1920's the expansion of the railroad system fostered the removal of the natural vegetation, which in turn was followed by the introduction of coffee, peanut, corn and cotton crops. This intense exploitation was conducted without respect to the soil carrying capacity and its natural susceptibility to erosional processes, including an aggressive form known as voçoroca. As a result, the study shows that the most susceptible material includes colluvium aprons, in situ regoliths, and colluvium-alluvium or alluvium deposits. The most critical situation is in the P2 Surface context, near the bottom of the Marília Plateau scarpment, where surface runoff can be very strong. Another point of active erosion is represented by the exposed walls of gullies and voçorocas, mainly in fluvial reaches subjected to talweg lowering. In a general sense, this study shows current evidence of erosional stability due to the ìntroduction of pastures as a predominant type of land occupation and to a series of erosion control procedures. Among these actions are terrace implantation, construction of small pits for runoff control, natural or induced reforestation by land owners. Despite these efforts, some erosion points remain chiefly in steeper country roads and trail stretches, in areas of concentration of cattle tracks (e.g., near cattle ponds), gullies or voçorocas exposed walls, and badly planned urbanization. The permanence of these erosion points demonstrates the necessity of a continuous monitoring of surface dynamics as well as a rapid and effective intervining measures of erosion and/or silting control.
Geoenvironmental analysis of the marília region, São Paulo state, Brazil: Erosive processes susceptibility face to the occupation area history
Keywords: Erosion; Erosion susceptibility; Geoenvironmental analysis; Regolith; Surface dynamics; Western são paulo state plateau; alluvial deposit; carrying capacity; colluvial deposit; Cretaceous; erosion control; fluvial deposit; human activity; land use; reforestation; regolith; runoff; sedimentary rock; terrace; urbanization; Brazil; Marilia; Sao Paulo [Brazil]; Arachis hypogaea; Bos; Gossypium hirsutum; Zea mays